ANALISIS KADAR ABU PADA SALAK MERAH (Salacca edulis) DI DESA RIRING DAN DESA BURIA KECAMATAN TANIWEL KABUPATEN SERAM BAGIAN BARAT, PROVINSI MALUKU - Smith, Alwi; Liline, Sintje; Sahetapy, Solagratia (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Background: Indonesia is a country suitable for growing salak plants. With this good climate it ispossible for types of plants and fruit to continue to grow and develop properly. in 100g of salak fruitflesh has a high nutritional content such as carbohydrates 20.9 g, calories 77.0 cal, protein 0.40 g,calcium 28.00 mg, phosphorus 18.0 mg, iron 4.20 mg, vitamin B 0.04 mg, vitamin C 2.00 mg andwater 78.00 mg.Methods: Testing the ash content using the dry ashing method. Ash content can show the totalminerals in a food ingredient.Results: The results showed that there was a difference between the ash content of red salak fruitin buria village and riring village. For Buria Village, the ash content of red salak fruit is 1.79535%. Asfor Riring Village, the percentage of ash content is 2.4744%.Conclusion: There are differences between the two samples of red salak fruit taken from 2 differentlocations. The effect of altitude is mainly related to plant metabolic processes, such as biochemicalprocesses and the synthesis of secondary metabolites, such as vitamins and minerals which affectthe size of the ash content in fruit.